The Sustainable Corporation - Famiola, Melia (SBM ITB, 2007)
The industrial sector is highlighted as the chief cause of the rapidly environmental change in the recent years. Because natural environment has strong correlation with human life and his activities to achieve well being, thereby industrial or business sector, the chief of human activities, is demanded to play as the central role in Sustainable Development. According to sustainable concept, there are three missions that have to be performed in sustainable development-sustainability in economics, environment and social. Of the three missions, environment and social are always taken in weak positions by business Actors. As the central actors in sustainable development, business actors should take the three of missions balance and together in their entire business activities. Based on same literatures and some successful stories in business practices, the author founded two important patterns that evolve recently how a corporation could be named as a suistanle corporation. First, the corporation developed partnership in eco-industrial part and the second; the corporation did its corporate social responsibility.Â Keywords:Â sustainability, sustainable corporation, , sustainable concept for business